PEDAGOGICAL CONDITIONS FOR FORMING READINESS FOR PROJECT ACTIVITY OF FUTURE SPECIALISTS IN RECREATION TOURISM (EDUCATION IN THE 21ST CENTURY, 2023)
Modern processes of reforming of the higher education system states as it’s goal renewal of the educational system as a whole, in order to ensure its optimal functioning. In this context, higher education institutions face that thy priority task is to provide highly professional training of specialists capable of ensuring the development of a democratic state. At the present stage of development of the educational system, there is a shift in the emphasis of the educational paradigm, from one focused on a certain level of knowledge into a developing one, which, accordingly, leads to the formation of various concepts of personality-oriented education. Project activity nowadays is the most common type of research practice of the students. The use of project activities in the educational process ensures the priority of socially significant knowledge and skills, implements the paradigm of personality-oriented education, since this knowledge and skills allow young people to be successfully implemented in their chosen professional activity. The practical use of project activities, in the process of training of future specialists in recreational tourism, provides an improvement in the quality of the educational process. Participants in the educational process are exposed to a number of factors, which, in turn, are determined by internal and external conditions. Taking into account the above, we will consider the presence of factors that ensure the maximum efficiency of the educational process, that is, pedagogical conditions, as an obligatory component of the process of forming readiness for project activities among future specialists in recreational tourism. The conducted research of scientific and pedagogical literature makes it possible to define that project activity belongs to the most common type of student research work. It is considered as an alternative to the classroom system in higher education institutions, while not completely replacing it. The content of the pedagogical conditions for the formation of the readiness of future specialists in recreational tourism for the use of project activities are determined based on the structure of readiness for such activities, which includes: motivational-target, operational, reflective and creative elements. The project readiness components have specific readiness levels, such as: initial, intermediate, advanced and high. We offer the following pedagogical conditions for the formation of readiness for project activities among future specialists in recreational tourism: the formation of students' motivation to use project activities in the educational process and future professional activities; ensuring the theoretical qualification of students for the implementation of project activities in the educational process; organization of the systematic and justified application of various types of project activities at different stages of the educational process.
Keywords: Keywords: pedagogical conditions, readiness for project activities, educational process, student-centered learning, future specialists in recreational tourism.